MEMBANGUN SISTEM INFORMASI WEBSITE DENGAN PENERAPAN METODE WATERFALL (STUDI KASUS : SMA XAVERIUS 5 BELITANG ) - Wisnumurti Wisnumurti; Sri Hartati (Jurnal Informatika dan Komputer (JIK), 2018)
By utilizing computer-based information technology with internet facilities, SMA Xaverius 5 Belitang builds an Information System that provides information about SMA Xaverius 5 Belitang. The purpose of this study is to build a website information system with the application of the Waterfall Method at SMA Xaverius 5 Belitang. The method used in the information system of SMA Xaverius 5 Belitang, as well as to find out which system is running, uses a structured approach using several tools such as Uml, use case diagrams, activity diagrams, sequence diagrams, class diagrams, while for the system development method using linear sequential or often referred to as the "classic development cycle" or "waterfall model". The supporting software used is Xampp, Adobe Dreamweaver CS3, PHP, and MySQL database as builders and program documentation and reports. In this information system, an interface page is provided for the admin to manage information data of SMA Xaverius 5 Belitang and has several interconnected pages, namely data about Home (Home), Profile, facilities, gallery, teacher data, student data, our contacts and books guest. Related Links which all provide information about SMA Xaverius 5 Belitang School to the public. With the delivery of information at SMA Xaverius 5 Belitang, which is accessed through internet media, it is expected to make it easier for people to find out information about SMA Xaverius 5 Belitang easier and faster to be accessed from anywhere and anytime without time limit, without having to visit SMA Xaverius 5 Belitang